The lantibiotic peptide labyrinthopeptin A1 demonstrates broad anti-HIV and anti-HSV activity with potential for microbicidal applications. - Geoffrey Férir (Public Library of Science (PLoS), 2013)
Lantibiotics are peptides, produced by bacteria, that contain the noncanonical amino acid lanthionine and many of them exhibit antibacterial activities. The labyrinthopeptin A1 (LabyA1) is a prototype peptide of a novel class of carbacyclic lantibiotics. Here, we extensively evaluated its broad-spectrum activity against HIV and HSV in vitro, studied its mechanism of action and evaluated potential microbicidal applications. LabyA1 exhibited a consistent and broad anti-HIV activity (EC50s: 0.70-3.3 µM) and anti-HSV activity (EC50s: 0.29-2.8 µM) in cell cultures. LabyA1 also inhibited viral cell-cell transmission between persistently HIV-infected T cells and uninfected CD4(+) T cells (EC50∶2.5 µM) and inhibited the transmission of HIV captured by DC-SIGN(+)-cells to uninfected CD4(+) T cells (EC50∶4.1 µM). Time-of-drug addition studies revealed that LabyA1 acts as an entry inhibitor against HIV and HSV. Cellular and virus binding studies combined with SPR/FLIPR technology showed that LabyA1 interacted with the HIV envelope protein gp120, but not with the HIV cellular receptors. LabyA1 also demonstrated additive to synergistic effects in its anti-HIV-1 and anti-HSV-2 activity with anti(retro)viral drugs in dual combinations such as tenofovir, acyclovir, saquinavir, raltegravir and enfuvirtide. LabyA1 can be considered as a novel lead peptide as it had profound antiviral activity against HIV and HSV. Pre-treatment of PBMCs with LabyA1 neither increased the expression of the activation markers CD69 and CD25, nor enhanced HIV replication, nor significantly induced various inflammatory cytokines/chemokines. LabyA1 also did not affect the growth of vaginal Lactobacilli populations. Based on the lack of toxicity on the vaginal Lactobacillus strains and its synergistic/additive profile in combination with clinically approved anti(retro)virals, it deserves further attention as a potential microbicide candidate in the prevention of sexual transmitted diseases.